2014
DOI: 10.1007/8904_2014_351
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Hematologic Manifestations of Gastric Intrinsic Factor (GIF) Deficiency: A Treatable Cause of B12 Deficiency in the Old Order Mennonite Population of Southwestern Ontario

Abstract: Intrinsic factor deficiency (OMIM #261000, IFD) is a rare inherited disorder of vitamin B 12 metabolism due to mutations in the gastric intrinsic factor (GIF) gene.We report three individuals from an Old Order Mennonite community who presented with B 12 deficiency. Two cases are siblings born to consanguineous parents and the third case is not known to be closely related. The older male sib presented at 4 years with gastrointestinal symptoms, listlessness, and pallor. He had pancytopenia with megaloblastic ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Classically, the Imerslund-Gräsbeck syndrome is mentioned as an example of a genetic cause of vitamin B 12 deficiency due to selective malabsorption, but its prevalence is very low. Other causes may be mutations in the gene for intrinsic factor, 70 genes encoding the vitamin B 12 transporting transcobalamins,71, 72 and genes involving intracellular vitamin B 12 metabolism. The list of single-nucleotide polymorphisms associated with serum vitamin B 12 concentration is gradually increasing, and a recent review reported 59 gene polymorphisms found in a wide variety of populations, although the majority were reported in people of Western European descent 37 .…”
Section: Familial/genetic Causes Of Vitamin B12 Deficiencymentioning
confidence: 99%
“…Classically, the Imerslund-Gräsbeck syndrome is mentioned as an example of a genetic cause of vitamin B 12 deficiency due to selective malabsorption, but its prevalence is very low. Other causes may be mutations in the gene for intrinsic factor, 70 genes encoding the vitamin B 12 transporting transcobalamins,71, 72 and genes involving intracellular vitamin B 12 metabolism. The list of single-nucleotide polymorphisms associated with serum vitamin B 12 concentration is gradually increasing, and a recent review reported 59 gene polymorphisms found in a wide variety of populations, although the majority were reported in people of Western European descent 37 .…”
Section: Familial/genetic Causes Of Vitamin B12 Deficiencymentioning
confidence: 99%
“…Gastric IF deficiency (also called megaloblastic anemia type 1 or congenital pernicious anemia) due to GIF mutations is a very rare Cbl absorption defect. Mutations in GIF result in functionally impaired or diminished IF or even in its complete absence and consequently, Cbl concentrations are low. In contrast to the much more frequent autoimmune‐mediated pernicious anemia of the adult, no IF/parietal cell antibodies are present.…”
Section: Inborn Errors Of Cbl Absorption and Systemic Cbl Traffickingmentioning
confidence: 99%
“…Some patients have achieved complete clinical and biochemical remission treated with as little treatment as 1 mg intramuscular OH‐Cbl twice per year. Two siblings with GIF deficiency (one asymptomatic with elevated MMA, one symptomatic in his first year) have responded favorably to oral treatment. Nevertheless, from a cohort of 19 patients older than 6 years with TC deficiency, only the one patient treated with oral Cbl had impaired intellectual function while patients on intramuscular hydroxo (OH)‐ or CN‐Cbl (mostly 1 mg weekly) had a favorable neurocognitive outcome.…”
Section: Inborn Errors Of Cbl Absorption and Systemic Cbl Traffickingmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 75 gr of meat can easily supply the daily vitamin B 12 demand but 1000 ml of milk is necessary for the same purpose [4]. According to novel data nearly 30% of patients older than 50 years have vitamin B12 deficiency and Health Canada recommend fortified foods for these patients [5]. Interestingly, Gout is more common after fifth decade and diet is an important and routine approach in management of patients with Gout.…”
Section: Introductionmentioning
confidence: 99%